2019
DOI: 10.1159/000502715
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low Birth Weight Predisposes to Impaired Renal Health: A Pooled Analysis

Abstract: Background: A number of studies examined the association between preterm delivery and kidney size and function later in life. However, the number of cases in published cohort studies is low. This study was aimed at performing a multicenter collaboration to pool data to obtain more accurate results to quantify the extent of renal impairment in former extremely low birth weight (ELBW; <1,000 g) children. Methodology: We performed a subject-level meta-analysis to pool data from Cracow (64 cases/34 controls) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
1
21
1
2
Order By: Relevance
“…In this meta-analysis, blood pressure was investigated by several studies [8,[24][25][26][27][29][30][31][32][33][37][38][39][40][41]43,44,[46][47][48], and the results were uniform in that the preterm-born group had higher SBP and DBP both in single-time and ambulatory monitored measures. These results were consistent with the previous meta-analyses [59][60][61][62]. Although SGA and AGA were not distinguished for their difference in most of the previous studies, our study showed that higher blood pressure associated with preterm survivors was observed only in the SGA and not in the AGA group.…”
Section: Discussionsupporting
confidence: 93%
“…In this meta-analysis, blood pressure was investigated by several studies [8,[24][25][26][27][29][30][31][32][33][37][38][39][40][41]43,44,[46][47][48], and the results were uniform in that the preterm-born group had higher SBP and DBP both in single-time and ambulatory monitored measures. These results were consistent with the previous meta-analyses [59][60][61][62]. Although SGA and AGA were not distinguished for their difference in most of the previous studies, our study showed that higher blood pressure associated with preterm survivors was observed only in the SGA and not in the AGA group.…”
Section: Discussionsupporting
confidence: 93%
“…This matters, as in ELBW infants, exposure to nephrotoxic drugs is common (87%) with gentamicin (86%), indomethacin (43%), and vancomycin (25%) as most commonly administered drugs ( 62 ). It is hereby important to highlight that follow-up of these populations remains important after hospital discharge as there are concerns on the long-term renal outcome, most pronounced in former ELBW cases ( 63 ). Research should focus on perinatal risk factors associated with impaired GFR in long-term outcome studies, but is hampered by single center cohorts, small samples sizes, and heterogeneity of GFR assessment tools ( 64 ).…”
Section: Renal Precision As Crucial Part Of Contemporary Neonatal Prementioning
confidence: 99%
“…An obvious next step is to pool based on the individual data. Such an effort should also facilitate the exploration of the association between perinatal characteristics (like birth weight, small for gestational age (SGA), Apgar score, indomethacin/ibuprofen or steroid use or gestational age) and GFR outcome, similar to the effort recently reported to pool the ELBW renal outcome data at the age of 11 years [22]. Second and at least as relevant, such pooling effort needs to consider the heterogeneity in GFR measurement (inulin, cystatin C or creatinine estimated GFR formulae) tools and assays (cystatin C, creatinine) used [6,22].…”
Section: Discussionmentioning
confidence: 99%